Analisis Implementasi Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah Pada UMKM Konveksi Jepara - Yanto; Risma Fajarani (Jurnal Rekoginisi Ekonomi Islam, 2023)
Most MSMEs cannot provide accounting information related to their business status because the financial reports prepared are not in accordance with SAK EMKM. The study aims to analyze the effect of business size, business age, owner's educational level on the implementation of SAK EMKM in Convection SMEs in Sendang Kalinyamatan Village, Jepara. The population is 506 SMEs, and the sample is 84 SMEs. Data analysis using multiple regression analysis. The results showed that business size had a significant positive effect on the implementation of SAK EMKM, as evidenced by the regression value (b1) = 0.100 with a sig. = 0.000; Business age has a significant positive effect on the implementation of SAK EMKM as evidenced by the regression value (b2) = 0.129 with a sig. = 0.013; The education level of the owner has a significant positive effect on the implementation of SAK EMKM as evidenced by the regression value (b3) = 0.576 with sig. = 0.001.